2013
DOI: 10.1177/2324709613504549
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Magnetic Resonance Imaging Findings of a Malignant Hepatic Epithelioid Hemangioendothelioma

Abstract: We report the case of a rare solitary small nodular form of malignant hepatic epithelioid hemangioendothelioma in a patient followed by computed tomography and gadoxetic acid (Gd-EOB-DTPA)–enhanced magnetic resonance imaging with histological analysis. This case showed early peripheral septal and nodular enhancement and delayed centripetal enhancing pattern with capsular retraction, mimicking peripheral cholangiocarcinoma, inflammatory pseudotumor, or metastases. The histological and immunohistochemical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…One study reported that 50% of the patients survived more than 5 years without any treatment, and the presence of metastasis did not prolong or shorten the survival rate[ 68 ]. Still, in other studies, successful hepatectomy or LT was shown to promote long-term survival[ 3 , 69 ], with 1- and 3-year disease-free survival rates of 83.3% and 44.4% after hepatectomy, respectively, as well as 1- and 5-year survival rates of 100% and 75%, respectively. The corresponding 1- and 5-year survival rates after LT were 96% and 54.5%, respectively[ 70 ], which were lower than those after hepatectomy due to the presence of multiple tumors or infiltrated foci in these cases.…”
Section: Prognosismentioning
confidence: 99%
“…One study reported that 50% of the patients survived more than 5 years without any treatment, and the presence of metastasis did not prolong or shorten the survival rate[ 68 ]. Still, in other studies, successful hepatectomy or LT was shown to promote long-term survival[ 3 , 69 ], with 1- and 3-year disease-free survival rates of 83.3% and 44.4% after hepatectomy, respectively, as well as 1- and 5-year survival rates of 100% and 75%, respectively. The corresponding 1- and 5-year survival rates after LT were 96% and 54.5%, respectively[ 70 ], which were lower than those after hepatectomy due to the presence of multiple tumors or infiltrated foci in these cases.…”
Section: Prognosismentioning
confidence: 99%
“…Overall, despite a lack of concrete guidelines regarding management, HEHE has a relatively good prognosis compared to other malignant tumors of the liver, with one study observing that metastasis did not appear to shorten the survival rate [ 14 ]. Other studies, however, have found interventions such as hepatectomy and liver transplantation to promote long-term survival [ 8 , 15 ]. Regardless, the presence of extrahepatic malignancy or metastasis, as seen in our patient, remains an absolute contraindication for liver transplantation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Las características más resaltantes a la evaluación por TC no contrastada (14) comprenden imágenes nodulares hipodensas (focos de atenuación disminuida, por la presencia de estroma mixoide, del parénquima hepático normal) coalescentes de ubicación periférica (en más del 75% de casos), con retracción de la cápsula (por fibrosis circundante e isquemia). El tamaño es variable, desde pequeños nódulos hasta grandes masas confluentes, algunas puedan presentar calcificaciones en su interior.…”
Section: Discussionunclassified